Bioalcohol production : biochemical conversion of lignocellulosic biomass - Waldron, K. W. (Woodhead Publishing in energy, 2010)
Bioethanol is one of the main biofuels currently used as a petroleum-substitute in transport applications. However, conflicts over food supply and land use have made its production and utilisation a controversial topic. Second generation bioalcohol production technology, based on (bio)chemical conversion of non-food lignocellulose, offers potential advantages over existing, energy-intensive bioethanol production processes. Food vs. fuel pressures may be reduced by utilising a wider range of lignocellulosic biomass feedstocks, including energy crops, cellulosic residues, and, particularly, wast.